Can Trust in Traditional News Media Explain Cross-National Differences in News Exposure of Young People Online?: A comparative study of Israel, Norway and the United Kingdom. Issue 2 (7th February 2018) - Elvestad, Eiri; Phillips, Angela; Feuerstein, Mira
Abstract : Using data from a cross-national survey (N = 940) and from in-depth interviews with 37 students in Israel, Norway and the United Kingdom, we discuss how in different political and news media environments young people's trust in traditional media can explain their news exposure online. This study shows there are some similarities, but also major cross-national differences, between young people in how they trust, are exposed to and find different news sources usable for information about their society. Students from all these countries have higher trust in traditional news media than in social media. However, young people in Norway living in high-trust environments tend to be exposed to a wider variety of news sources than the UK and Israeli students. They also tend to be more skeptical about social media as a useful source of information. Furthermore, this study suggests that in a national context of conflict and low trust in media, such as Israel, distrust in traditional news media can explain foreign news exposure online. However, the effect of trust in national media is not significant in the Norwegian and the UK sample, which highlights the importance of discussing online news exposure in different national political and media environments.